Clinical and epidemiological features of congenital epidermolysis bullosa in the Republic of Dagestan - K. M. Gadzhimuradova; M. A. Ivanova; M. N. Gadzhimuradov; S. N. Alieva (Лечащий Врач, 2022)
Congenital epidermolysis bullosa refers to orphan (rare – no more than 10 cases per 100,000 population) diseases. In the Russian Federation, its prevalence rate in 2016 was 3,9 per 1 million population. The objective was to study the clinical and genetic characteristics, prevalence, and family history of сongenital epidermolysis bullosa patients in the Republic of Dagestan. The clinical picture, features of the course and family history of 127 patients with the diagnosis of сongenital epidermolysis bullosa living in the Republic of Dagestan were studied, and the type and subtype of the disease were verified. In 12 patients, the genetic nature of сongenital epidermolysis bullosa was confirmed by full-exomal DNA sequencing. According to the severity of сongenital epidermolysis bullosa, patients were divided into four groups. Most of them were in the group with mild to moderate severity: Weber – Cockayne сongenital epidermolysis bullosa – 53 (41,73 ± 4,38%, n = 127) and Dowling – Mear herpetiform – 11 (8,66 ± 2,5%, n = 127), dominant dystrophic congenital epidermolysis bullosa – 3 (2,36 ± 1,35%, n = 127) and recessive generalized non – mutating dystrophic congenital epidermolysis bullosa – 1 (0,79 ± 0,79%, n = 127), borderline dystrophic congenital epidermolysis bullosa – 8 (6,3 ± 2,16%, n = 127), and Kindler syndrome – 1 (0,79 ± 0,79%, n = 127). Patients with generalized recessive dystrophic congenital epidermolysis bullosa were included in the group with severe or very severe course-7 (5,51 ± 2,07%, n = 127) and 21 (16,54 ± 3,32%, n = 127), respectively. More than half of the cases of congenital epidermolysis bullosa in the Republic of Dagestan (63,78 ± 4,26%) were children, up to 6,3 ± 2,16% were aged from 56 to 63 years, which required a differentiated approach in their management. The majority of patients with recessive dystrophic congenital epidermolysis bullosa and borderline dystrophic congenital epidermolysis bullosa had closely related parental marriages, which was most typical for 12 districts of the Republic.